Build, borrow, or buy : solving the growth dilemma - Capron, Laurence. (Harvard Business Review Press, 2012)
How should you grow your organization? It is one of the most challenging questions an executive team faces and the wrong answer can break your firm. The problem is most firms' growth strategies emphasize just one type of growth but firms falling into this implementation trap usually end up losing out to a competitor whose approach is more inclusive. Drawing on decades of research and teaching, the authors find that a firm's aptitude for determining the best resource pathways for growth has a defining impact on its success. They have come up with a helpful framework, reflecting practices of a variety of successful global organizations, to determine which path is best for yours. Written for large multinationals and emerging firms alike, this book will help solve a perennial question and will guide you through change while priming your organization for optimal growth.